The Law and policy of air space and outer space : a comparative approach - Haanappel, P. P. C. (Kluwer Law International The HagueNL, 2003)
Discusses briefly, the historical origins of air law and space law. Looks at the question of natural sovereignty or the absence thereof in airspace and in outer space. Highlights intergovernmental and non-governmental organisations active in the fields of air and space law. Focuses on public airspace law and private aerospace law as well as in air transport law and policy. Looks at commercial outer space activities.